Pobożność maryjna w kontekście pism Johna Henry’ego Newmana - Majewska-Michy, Justyna (Studia Europaea Gnesnensia, 2018)
The article seeks to answer whether John Henry Newman (1801-1890), outstanding theologian of nineteenth-century England and a Catholic convert, was particularly worshipful of Holy Virgin Mary. He would express his piety towards the Blessed Virgin, revered as the Mother of God, through his writings. The author thus analyzes the publications from the Anglican and the Catholic periods in Newman’s life, in which the latter referred to the Mother of the Word Incarnate. In his sermons, essays, speeches, lectures and letters, the eminent representative of the English Church conveys his attitude to the Mother of God.